Antibacterial Activity of Bacteriocin Like Compound Extracted from Lactic Acid Bacteria Isolated from Farm Soil, Curd, and Gundruk - Sigdel, Anshuya; Thapa Magar, Anita; Khadka, Rama (Tribhuvan University Journal of Microbiology, 2025)
Objectives: This study was focused on examining the antimicrobial properties of bacteriocin like compound extracted from Lactic acid bacteria (LAB) isolates from curd, farm soil, and Gundruk samples. Methods: A total of 30 samples of farm soil (10), curd (10) and Gundruk (10) were collected from a Kathmandu district and identified strains of LAB. Dot plate technique was used for screening of bacteriocin, then bacteriocin was extracted from precipitation method. Antimicrobial activity was done from cell-free suspension by Agar well diffusion method. Results: In this study, 86% of LAB were isolated and identified as Streptococcus species (46.67%), Lactobacillus species (23.33%) and Pediococcus species (16.67%). Out of the 26 isolates, 7 isolates (23.33%) produced bacteriocin. The antibacterial activity demonstrated inhibition zones ranging from 7–16 mm for farm soil isolates, 10–20 mm for curd isolates, and 7–18 mm for Gundruk isolates. From mixed extraction of bacteriocin (1:1 of Pediococcus spp. and Streptococcus spp.), antibacterial activity was shown to all test bacteria except S. aureus ATCC 43300. Conclusion: This study concluded that LAB isolates from Gundruk exhibited the highest antibacterial activity (18–21 mm), compared to farm soil and curd isolates, highlighting their potential as a more effective natural antimicrobial source.